Palliative Care in Undergraduate Medical Education—How Far Have We Come?. (September 2017) - Fitzpatrick, Danielle; Heah, Rebecca; Patten, Simon; Ward, Helena
Purpose: There is an increasing demand for quality palliative care teaching within undergraduate medical education. Studies suggest that many junior doctors feel underprepared to perform end-of-life care. Previous systematic reviews on palliative care teaching within medical schools have identified significant variability and lack of consistency in teaching. This review aims to update the literature on the current status of palliative care teaching to undergraduates within medical schools. Method: A systematic review was undertaken on articles published from December 2001 to November 2015 on palliative care teaching for undergraduate medical students. In all, 650 abstract citations were obtained, of which 126 were relevant to the research questions. Thematic analysis was performed on remaining articles according to whether they discussed content and/or methodology of palliative care education, and data collated. Results: There is greater consistency in the content being delivered as part of end-of-life care education within medical schools. The most frequently taught topics include attitudes to death and dying, communication skills, and pain management. Pediatric care and religious/cultural issues are less frequently addressed. Teaching institutions are also utilising a broader range of teaching modalities. Conclusion: There is significant progress in palliative care education within medical schools. Ongoing challenges relate to correlating our current practice in medical education to professional recommendations and the expressed needs of junior doctors to practice competent end-of-life care.